PENERAPAN FUNGSI PASTORAL KONSELING DALAM BUDAYA MEPALOS’E - Melkisedek Teleng (MATHESI: Jurnal Pendidikan dan Bimbingan Konseling, 2026)
This study aims to examine and explain the application of pastoral counseling functions, particularly the sustaining function, within the framework of the values contained in the Mepalos’e Culture in the Sangihe Islands Regency. This study employs a qualitative method with a literature review approach to explore relevant theological concepts and local wisdom. The results show that generally, pastoral counseling functions include healing, sustaining, guiding, reconciling, and nurturing as a form of holistic ministry. Specifically, the sustaining function plays a vital role in accompanying those who are experiencing life crises by being present, providing support, helping them accept new realities, and rediscovering the meaning of life. The Mepalos’e Culture, which is rooted in the principle of mutual support and sharing burdens, has a strong alignment with the essence of this pastoral function. This proves that the application of pastoral ministry adapted to local culture becomes more relevant, easily accepted, and effectively addresses the spiritual and social needs of the community in a deeper manner.